Construction of RC staircase for fire exit route at Petronas Research Sdn Bhd, Bangi / Muhammad Badri Maarof - Maarof, Muhammad Badri (2017)
Staircase have been created to ease on access from one to one point in different height. The role of the staircase is on connecting different levels in the shortest and yet convenient way possible.The materials used are depends on client’s request. Most commonly used are wooden and RC staircase. Types of staircase are also differ such as Straight, Spiral, Winder, 2 Quarter Winder, 2 Quarter Landing, Curved, Half Landing and Double Winder. This report is a study on constructing a Straight type RC Staircase for fire escape purpose at Petronas Resarch Sdn. Bhd. (PRSB), Bangi. Some aspect needs to be considered are Personal Protective Equipment of the workers. There are several requirements or laws that need to be followed according to Universal Building By-Law (UBBL). The objective of the study is to obtain the process and step-by-step of constructing a staircase with according to client’s need. Also, not ignoring the safety of the workers, standards and laws related to the construction of staircase. This study will also explain on the elements of the staircase.